Empowerment of Chicken Farmers Based on Cleaner Production and Strengthening of Product Added Value through Entrepreneurial Knowledge Enhancement - Hermawan , Iwan; Suharmanto, Suharmanto; Hindrawati, Gita; Sartono, Sartono; Inayah, Inayah; Pratama, Bagas (Mitra Edukasi dan Publikasi, 2024)
Given the environmental and health challenges, chicken poultry farms are now facing an increasing urgency to implement cleaner production. The application of the Cleaner Production concept is expected to be a solution to increase business efficiency and sustainability. One way is to process chicken poultry farm waste into valuable products, such as organic fertilizers, thereby reducing environmental negative impacts. This research method uses a Research and Development (R&D) approach with a three-box method. The community participates in a training program focusing on the innovation of processed chicken products, namely the manufacture of dimsum. This training covers theory and practices about Cleaner Production and dimsum-making techniques. The method used in building a complete solution in community service was obtained by Borg and Gall with the calculation of a questionnaire used to measure the achievement of induction of knowledge and skills based on the three-box method. The implementation of community service programs has shown an increase in the skills of partner Small and Medium Enterprises (SMEs) by 89%, an increase in knowledge by 97.6%, and the development of ideas for sustainability by 98.8%. This community service provides a complete solution to increase cleaner production, effectively improving skills and adding value to UD Sumber Mandiri processed chicken products.